2021
DOI: 10.1021/acsomega.0c05950
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cell-Based Assay to Investigate Monoacylglycerol Acyltransferase 2 Inhibitory Activity Using HIEC-6 Cell Line

Abstract: The dietary triacylglycerol (TAG) gets absorbed and accumulated in the body through the monoacylglycerol (MAG) pathway, which plays a major role in obesity and related disorders. The main enzyme of this pathway, monoacylglycerol acyltransferase 2 (MGAT2), is considered as a potential target for developing antiobesity compounds. Hence, there is a need for in vitro cell-based assays for screening the potential leads for MGAT2 inhibitors. Because of synthetic inhibitor's side effects, there is an increased intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Similar findings were also reported by [ 18 , 19 , 21 , 55 ] who studied the polyphenolic composition of some spice extracts. Furthermore, it is observed that DPPH and ABTS tests were positively correlated since Pearson’s correlation coefficient was R = 0.97 ( p ≤ 0.05) between the assays ( Table S1 ), in line with previous studies [ 56 , 57 , 58 ]. Since DPPH is only applicable to hydrophobic systems due to the use of a radical dissolved in organic media, the strong correlation with ABTS indicated that additional and less hydrophilic compounds may also contribute to the scavenging effect [ 59 ].…”
Section: Resultssupporting
confidence: 89%
“…Similar findings were also reported by [ 18 , 19 , 21 , 55 ] who studied the polyphenolic composition of some spice extracts. Furthermore, it is observed that DPPH and ABTS tests were positively correlated since Pearson’s correlation coefficient was R = 0.97 ( p ≤ 0.05) between the assays ( Table S1 ), in line with previous studies [ 56 , 57 , 58 ]. Since DPPH is only applicable to hydrophobic systems due to the use of a radical dissolved in organic media, the strong correlation with ABTS indicated that additional and less hydrophilic compounds may also contribute to the scavenging effect [ 59 ].…”
Section: Resultssupporting
confidence: 89%